Fostering a Knowledge Culture for Peace, Development, and Integration: Muslim Education in the Philippines - Alizaman D. Gamon; Mariam Saidona Tagoranao (Studia Islamika, 2022)
The study delves into discussions addressing the development of knowledge culture and its implications for peace and sustainable development within the Philippines. The research also looks at government policies and procedures for advancing cultural and civilizational relationships. The research seeks to explore routes for integrating knowledge initiatives that would put Muslim education in a new favorable light in the eyes of humanity by utilizing original materials such as government data, unpublished publications, and interviews. The paper recommends that the tawhidic approach be acknowledged and used to build bridges and channels of academic, scientific, and technical collaboration with other systems and educational institutions at both the local and national levels. In conclusion, the study develops the concept of knowledge integration in serving the interests of the country and beyond.